2014
DOI: 10.1016/j.scico.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and design of a service-based framework to integrate personal and institutional learning environments

Abstract: h i g h l i g h t s• LMS and PLE are going to coexist and they should interact.• Existing initiatives don't support a complete interoperability among these contexts.• A service-based framework to facilitate this interoperability is defined.• It includes several interoperability scenarios that are tested in the university.• Interoperability between PLE and LMS is possible. a r t i c l e i n f o a b s t r a c t The landscape of teaching and learning has changed in recent years because of the application of Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…On the contrary, the learning buckets showed to be an effective and flexible solution that can be embedded in widespread VLEs such as Moodle, transforming them in across spaces learning environments integrated with multiple common Web 2.0 tools and mobile AR clients. Other approaches in the literature also propose solutions for combining existing VLEs and activities in other physical and virtual spaces (e.g., Conde et al, 2014;León Font, 2014;Santamarina et al, 2010;Zhang et al, 2010), but do not include context-awareness features, which limits the alignment orchestration aspect (see Section 2). As an alternative for overcoming such limitation, the evaluation showed that the learning buckets can be a simple instrument to connect the different physical and virtual spaces, by enabling the access from a space to contextualized artifacts created in another space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the learning buckets showed to be an effective and flexible solution that can be embedded in widespread VLEs such as Moodle, transforming them in across spaces learning environments integrated with multiple common Web 2.0 tools and mobile AR clients. Other approaches in the literature also propose solutions for combining existing VLEs and activities in other physical and virtual spaces (e.g., Conde et al, 2014;León Font, 2014;Santamarina et al, 2010;Zhang et al, 2010), but do not include context-awareness features, which limits the alignment orchestration aspect (see Section 2). As an alternative for overcoming such limitation, the evaluation showed that the learning buckets can be a simple instrument to connect the different physical and virtual spaces, by enabling the access from a space to contextualized artifacts created in another space.…”
Section: Discussionmentioning
confidence: 99%
“…Their approach enables the integration of mobile games as any other activity in a course within the VLE. Another interesting approach is the architecture proposed by Conde, García-Peñalvo, Alier, Mayol, and Fernández-Llamas (2014) for integrating Personal Learning Environments (PLEs) with VLEs, enabling also the access to different activities and tools from mobile devices. A slightly different approach is the work carried out by Hernández-Leo et al (2012) integrating their Signal Orchestration System (SOS) with Moodle (León Font, 2014).…”
Section: Approaches Using Vles In Bricolage Mode and Limitations For mentioning
confidence: 99%
“…In an attempt to give the student the total control of his / her learning space, while allowing the registration of all learning activities, [29] suggest a possible solution to integrate the static nature of Learning Management Systems in the dynamic notion of a Personal Learning Environment. The author designates it a service-based framework.…”
Section: Related Workmentioning
confidence: 99%
“…With the continuous development of E-business, the focus of E-business is gradually moved from the initial B2C to more challenging B2B [1]. In order to let enterprises to obtain highly efficient business, increase the income and reduce costs for getting greater business and competitive returns, the designers of E-business solution scheme need consider crossing different network configuration from the various private internal network of enterprises to Extranet of sharing information data among them [2].…”
Section: Introductionmentioning
confidence: 99%